2017
DOI: 10.12691/ajfn-5-3-6
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Quality Assessment of Fish Powder

Abstract: The study carried out with a view to determining proximate and mineral composition of fish powder of five freshwater fish samples (Hypophthalmicthys molitrix, Labeo rohita, Cirrnina mrigala and Puntius sophore and small prawns). The samples collected from five local fish markets of Rajshahi city corporation were subjected to washing, gutting drying and grinding in order to make powder and homogenized sample which were preserved into plastic container for chemical analyses. All the activities were conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 5 publications
(8 reference statements)
2
9
2
Order By: Relevance
“…The ash content of the five developed dried fish powders ranged from 7.66% to 9.19% ( Table 2). The highest content of ash was found in the sample P. puntio (9.19%) [11]. Our study resembles with study [43] where they found the ash content of dried burrito fish powder (14.0%) which is mostly consistent with our study.…”
Section: Ashsupporting
confidence: 92%
See 3 more Smart Citations
“…The ash content of the five developed dried fish powders ranged from 7.66% to 9.19% ( Table 2). The highest content of ash was found in the sample P. puntio (9.19%) [11]. Our study resembles with study [43] where they found the ash content of dried burrito fish powder (14.0%) which is mostly consistent with our study.…”
Section: Ashsupporting
confidence: 92%
“…Our investigation also found that the moisture content of L. rohita was below the study by [42] in which they found the moisture contents of L. rohita 9.07%. Another study [39] determined that the mois- .50%, which is significantly greater than our investigation [11]. Moreover, our findings are below the research by [11] where they found the moisture content of dried H. molitrix (13.95%) and L. rohita (11.55%) which are greater than our investigation.…”
Section: Moisturecontrasting
confidence: 87%
See 2 more Smart Citations
“…In general, this research found significant variations between the compositions of the different dried fish products. Similar reports have been reported from previous studies [12,13,15]. The observed variation in composition could be due to various factors such as species, sex, maturity state, feeding condition and seasonal variations.…”
Section: Proximate Compositionsupporting
confidence: 90%